Rancang Bangun Aplikasi Pengiriman Barang Dengan Rute Terpendek Menggunakan Metode Ant Colony Optimization Pada PT Saka Mitra Usaha - Yohanes Krisantoro Adjie; Julianto Lemantara; Agus Dwi Churniawan (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
PT Saka Mitra Usaha is a snacks intermediary towards small shop delivered by a motorist. The motorist doesn't have any clear guidelines regarding closest delivery route, which makes it possible that the route followed is not the closest one and more time will be wasted during travel made. The solution proposed is to make an android based application that gives a closest route reccomendation to solve this problem, which is a Traveling Salesman Problem, where a courier needs to deliver items with the closest route as possible. The method chosen is Ant Colony Optimization, mainly the Ant System variant. Ant System is chosen because it has a lot of variables that can be modified in order to reach closest route, and also because the number of shop used is only 15 shops. The test results for 15 shops shown that the closest route available is 40.343 kilometers, reached using 8 ants and a combination of a = 1.5, β =1, ρ = 0.9 or a = 2, β =1.5, and ρ = 0.5-0.9. The application also gives the closest route recommendation and navigation helper in order to give the best route possible and shorten travel time.